Implicit Microfoundations for Macroeconomics - Ian Wright (Kiel Institute for the World Economy (IfW), 2008)
A large market economy has a huge number of degrees of freedom with weak microlevel coordination. The 'implicit microfoundations' approach assumes this property of micro-level interactions more strongly conditions macro-level outcomes compared to the precise details of individual choice behavior; that is, the 'particle' nature of individuals dominates their 'mechanical' nature. So rather than taking an 'explicit microfoundations' approach, in which individuals are represented as 'white-box' sources of fully-specified optimizing behavior (rational agents), we instead represent individuals as 'black box' sources of unpredictable noise subject to objective constraints (zero-intelligence agents). To illustrate the potential of the approach we examine a parsimonious, agent-based macroeconomic model with implicit microfoundations. It generates many of the reported empirical distributions of capitalist economies, including the distribution of income, firm sizes, firm growth, GDP and recessions.
Keywords: E11; P16; D50; C63; B41; A12; 330; Micro foundations; macroeconomics; aggregation; power laws; Mikroökonomische Fundierung; Agent-based Model; Aggregation; Makroökonomik; Marktwirtschaft; Wahrscheinlichkeitsrechnung; Theorie